The Relationship between Theory and Practice: An Examination Based on Pre-Service Teachers' Beliefs - Emel BAYRAK OZMUTLU (Anı Publishing, 2022)
The purpose of this study is to conduct an examination based on pre-service teachers' beliefs about the theoretical content of teacher education programmes. The research was carried out with a basic qualitative research design. The study group of the research was determined with the criterion sampling method, which is one of the purposive sampling methods. The study group of the research consisted of 134 pre-service teachers studying in three different programmes in their eighth semester. Analyses were performed on belief statements labelled with 582 in vivo codes. An extensive and detailed analysis process consisting of three stages was followed in the research. The research shows that the highest rate of pre-service teachers' beliefs about the functions of theoretical content were in the remembering category. Pre-service teachers' beliefs about the dysfunctionality of theoretical content mostly reflected their preconceptions about theoretical content. Beliefs about how the dysfunctionality of theoretical content could be overcome were related to the need to solve the problems of trust, permanence and context in teacher education programmes. In teacher education programmes, pre-service teachers need to focus on ways to deal with the functions of theoretical content at the metacognitive level and to overcome their preconceptions about theoretical content.